2000
DOI: 10.1101/lm.34200
|View full text |Cite
|
Sign up to set email alerts
|

PACAP-38 Enhances Excitatory Synaptic Transmission in the Rat Hippocampal CA1 Region

Abstract: Specific receptors for pituitary adenylate cyclase-activating polypeptide (PACAP), a novel peptide with neuroregulatory and neurotrophic functions, have been identified recently in different brain regions, including the hippocampus. In this study, we examined the effects of PACAP-38 on the excitatory postsynaptic field potentials (fEPSPs) evoked at the Schaffer collateral-CA1 synapses. Brief bath application of PACAP-38 (0.05 nM) induced a long-lasting facilitation of the basal transmission. Enhancement of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…Previously, we found that 0.05 nM PACAP-38 produced a long-lasting enhancement of basal CA1 fEPSPs and that this enhancement was occluded by previous induction of LTP by high frequency stimulation (HFS) (Roberto and Brunelli 2000). In the present study, we examined the converse experiment (i.e., whether previous treatment with PACAP-38 would occlude LTP).…”
Section: Tetanic Stimulation Fails To Induce Ltp After Pacap-38-inducmentioning
confidence: 88%
See 4 more Smart Citations
“…Previously, we found that 0.05 nM PACAP-38 produced a long-lasting enhancement of basal CA1 fEPSPs and that this enhancement was occluded by previous induction of LTP by high frequency stimulation (HFS) (Roberto and Brunelli 2000). In the present study, we examined the converse experiment (i.e., whether previous treatment with PACAP-38 would occlude LTP).…”
Section: Tetanic Stimulation Fails To Induce Ltp After Pacap-38-inducmentioning
confidence: 88%
“…Previously, we reported that brief bath application of 0.05 nM of PACAP-38 induced a long-lasting enhancement of the Schaffer collateral-commissural CA1 fEPSP, whereas PACAP-38 produced only a transient increase in the evoked responses after LTP was saturated (Roberto and Brunelli 2000). In those studies atropine blocked both facilitatory effects (Roberto and Brunelli 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations